Woody Plants Interaction with Aerosol Fine Particulate Matters and Copper in Budapest - Chen, Haimei; Kardos, Levente; Szabo, Veronika; Magdolna, Diószegi; Honfi, Peter (Journal of Environmental Geography, 2023)
Ambient particulate matter pollution is the primary concern as it has a significant impact on human health and the majority of the world’s population lives in urban areas. Heavy metals are the most concerning component of particulate matter, and Cu is a highly traffic-related emission element whose overabundance results in toxic effects. Woody plants, on the other hand, contribute to the removal of airborne pollution in urban areas. Our aims are (1) to compare urban woody plants abilities to capture ambient fine particulate matter on leaf surface; and (2) to access the Cu concentration loads on their leaf surfaces. Consequently, our results will provide scientific knowledge for future urban planning concerning air pollution remediation. We investigated the relationship between woody plants and heavy metal pollution in Budapest. Four woody plant species were sampled at different traffic densities. Their Cu contents in the leaf and branch were measured, our results show that Tilia tomentosa and Acer platanoides are better options for ambient Cu accumulation than Fraxinus excelsior and Aesculus hisppocastanus in urban environments. At different traffic densities and sampling times, however, Cu accumulation did not vary across species. This is because, through translocation, woody plants absorb Cu not only from the air but also from the soil. Furthermore, it is also because of the long-distance transportation and long-term suspension of fine particulate matter. From the obtained results, we can conclude that woody plants are important phytoremediation elements in the urban area of Budapest. Planting T. tomentosa and A. platanoides in urban areas of central Europe will be promising for ambient heavy metal pollution phytoremediation. But environmental conditions differ from one place to another. Therefore, a comprehensive study is required in order to apply the results to different locations.